Students’ Perceptions of the Integration of Local Cultural Values in Higher Education: A Quantitative Study in South Sumatra, Indonesia - Destriani, Destriani; Indrawati, Indrawati; Indaryanti, Indaryanti; Deskoni, Deskoni; Purnomo, Mulyadi Eko (AL-ISHLAH: Jurnal Pendidikan, 2026)
The integration of local cultural values in higher education has gained increasing attention as a strategy to strengthen students’ character and cultural identity in the context of globalization. However, empirical evidence on how students perceive and engage with such integration remains limited, particularly in Indonesian higher education. This study aims to examine students’ understanding, participation, and perceived influence of local cultural values on character development.This research employed a quantitative correlational survey design involving 271 undergraduate students from two universities in South Sumatra, Indonesia. Data were collected using a structured questionnaire with a 4-point Likert scale. Descriptive statistics were used to analyze students’ perceptions, while Pearson correlation analysis was conducted to examine relationships among variables.The findings indicate that students demonstrate a high level of understanding and positive perceptions of local cultural values integrated into the learning process. Participation in culture-based activities is also relatively high, although some variability exists. Furthermore, students perceive local cultural values as highly relevant to character formation and daily behavior. Correlation analysis reveals significant positive relationships between understanding, participation, and character development, suggesting that greater engagement with cultural values is associated with stronger character outcomes.In conclusion, the integration of local cultural values in higher education contributes positively to both cognitive and behavioral aspects of student development. However, enhancing institutional support and expanding cultural programs are necessary to optimize implementation. These findings highlight the importance of culturally responsive education in fostering well-rounded and culturally grounded graduates.